3D Kinect Camera Scheme with Time-Series Deep-Learning Algorithms for Classification and Prediction of Lung Tumor Motility - Utumporn Puangragsa; Jiraporn Setakornnukul; Pittaya Dankulchai; Pattarapong Phasukkit (Sensors, 2022)
) of 1.2-1.6%, 0.65-0.8%, and 0.97-0.98, respectively. The results demonstrate that the time-series deep-learning classification and regression-based prediction models can classify the respiratory phases and predict the lung tumor displacement with high accuracy. Essentially, the novelty of this research lies in the use of a low-cost 3D Kinect camera with time-series deep-learning algorithms in the medical field to efficiently classify the respiratory phase and predict the lung tumor displacement.
Keywords: Lung Cancer Diagnosis and Treatment; Advanced Radiotherapy Techniques; Non-Invasive Vital Sign Monitoring